Management - Daft, Richard L.; Benson, Alan (Cengage Learning, 2016)
Fully updated and restructured to reflect the needs of students and lecturers on management courses in Europe, the Middle East and Africa, this title focuses on Europe, Middle East and Africa to reflect the global nature of this subject whilst maintaining the comprehensive coverage of various management theory and practice